PLEIOTROPIC EFFECTS OF VITAMIN D - O. M. Drapkina; R. N. Shepel (Столичная издательская компания, 2016)
Review of clinical studies showing the pleiotropic effect of vitamin D with a detailed description of pathogenetic ways to implement these effects  is presented. Relation of vitamin D with cardiovascular diseases, kidney diseases, disorders of the immune and nervous systems, aging is discussed according to results of current researches.